Copper and iron metabolism in Ostreococcus tauri - the role of phytotransferrin, plastocyanin and a chloroplast copper-transporting ATPase - Scheiber, Ivo Florin; Pilátová, Jana; Malych, Ronald; Kotabova, Eva; Krijt, Matyáš; Vyoral, Daniel; Mach, Jan; Léger, Thibaut; Camadro, Jean-Michel; Prášil, Ondřej; Lesuisse, Emmanuel; Sutak, Robert (Metallomics, 2019)
Iron and copper are essential elements for practically all living organisms. Their metabolism is frequently interconnected, and while copper is relatively abundant in the ocean, iron is often a limiting factor for the growth of many marine microorganisms. In the present study, we aimed to elucidate the metabolisms of copper and iron and the connection of both in the marine picoalga Ostreococcus tauri. We show that O. tauri adjusts its copper economy in response to copper deficiency by downregulation of the expression of plastocyanin in favor of cytochrome c oxidase without significant changes in growth and physiology. Copper deprivation leads to increased expression of copper transporting ATPase and proteins involved in tetrapyrrole synthesis, most likely to ensure higher turnover of chlorophyll and/or heme. Elucidation of the effect of copper on the incorporation of iron into O. tauri proteins led us to identify the major iron uptake mediating protein, Ot-Fea1, whose expression and binding of iron is copper dependent. Based on our investigation of the incorporation of iron into Ot-Fea1 and ferritin, we hypothesize that O. tauri possesses another Fea1-independent iron uptake system.
Keywords: železo; Copper-Transporting ATPases; transferin; Chlorophyta; plastocyanin; měď; ATPasy transportující měď; Copper; Chloroplasts; Transferrin; Iron; Plant Proteins; chloroplasty; Plastocyanin; rostlinné proteiny